Automatización del sistema contra incendios de la planta envasadora Lojagas. - Armijos González, Franco Vinicio (2008)
The main object of this work is to design and implement an automation architecture for efficient fire control system, which must prioritize simplicity and flexibility as first choice and reasonable costs For this task and following the methodological guidelines of this research, a full lifting of the object of study was developed, taking into account each of the instruments, electrical drawings, operating manuals and existing performance in the bottling of LPG lojagas as well as various stages of operation with counting system fire, then, to make a very thorough of the major factors directly involved in the fire system efficiency study. This research is structured as follows: Theoretical aspects and technicians to be present and exposed in Chapter I. Overview of the bottling plant Lojagas, a detailed description of the control architecture proposed and implemented in the automation system of Chapter II. System Monitoring Chapter III control. A brief technical evaluation of bids set out in Chapter IV, and finally conclusions and recommendations.